Pengaruh Umur Panen terhadap Hasil Ubi Jalar Cilembu pada Tanah PMK - Fernando, Lexy; Supriyanto, Supriyanto; Arifin, Nur (Perkebunan dan Lahan Tropika, 2025)
Sweet potato (Ipomoea batatas L.) is a widely cultivated crop in Indonesia, valued for its high economic potential and versatility. The Cilembu variety, originating from West Java, has been recognized for its high yield potential. This study aimed to determine the optimal harvest time for Cilembu sweet potatoes grown on PMK soil. Conducted from September 2024 to February 2025, the research employed a completely randomized design (CRD) with five treatments (harvest times: 3, 3.5, 4, 4.5, and 5 months) and four replications. Variables observed included fresh weight, dry weight, tuber weight, diameter, number of tubers, sugar content, moisture content, and fiber content. Results showed that harvest time significantly affected tuber diameter, tuber weight, and sugar content. The study concluded that harvesting at 4 months yields optimal tuber weight and diameter with standard fiber and moisture content, while the highest sugar content was achieved at 3.5 months. This research contributes to optimizing sweet potato cultivation practices, enhancing yield quality and quantity